Visual Representations of Music in Three Cultures: Commentary on Athanasopoulos and Moran - Tan, Siu-Lan (Empirical Musicology Review, 2013)
Athanasopoulos and Moran (2013) examined visual representations of brief melodic sequences (solo synthesized flute playing rising, falling, peak, and valley pitch contours) by British participants familiar with western standard notation, Japanese participants familiar with Japanese standard notation, and participants from the BenaBena tribe in Papua New Guinea who were unfamiliar with any literary or notational script. This commentary discusses the method, analysis, and implications of the findings, within the context of a multidirectional gain/loss perspective of the acquisition of skills in human development, as applied to musical notation.